Literature review writing: a study of information selection from cited papers / Kokil Jaidka, Christopher Khoo and Jin-Cheon Na - Jaidka, Kokil Jaidka; Khoo, Christopher Khoo; Na, Jin-Cheon Na (2011)
This paper reports the results of a small study of how researchers select and edit research information from cited papers to include in a literature review. This is part of a bigger content analysis and linguistic analysis of literature reviews. This study aims to answer the following questions: where do authors select information from the cited papers (e.g., Abstract, Introduction, Conclusion section, etc.)? What types of information do they select (e.g., research objectives, results, etc.), and How do they transform that information (e.g., paraphrasing, cut-pasting, etc.)? In order to answer these questions, we analyzed the literature review section of 20 articles from the Journal of the American Society for Information Science & Technology, 2001-2008, to answer these questions. Referencing sentences were mapped to source papers to determine their origin. Other features of the source information were also annotated, such as the type of information selected and the types of editing changes made to it before including into the literature review. Preliminary results indicate that authors prefer to select information from the Abstract, Introduction and Conclusion sections of the cited papers. This information is transformed through cut-paste, paraphrase or higher-level semantic transformations to describe the research objective, methodology and results of the referenced study. The choices made in selecting and transforming the source information appeared to be related to the two styles of literature review finally constructed – integrative and descriptive literature reviews. Keywords: Literature reviews; Multi-document summarization; Information science; Information extraction; Information selection.